Analisis Produktivitas Kegiatan Penelitian Dosen di Universitas Muhadi Setiabudi - Muhammad Syaifulloh; Farhan Saefudin Wahid; Nasiruddin Nasiruddin (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
Lecturer Functional Position is an Academic Position system that is obtained through submissions covering Tri Dharma activities in tertiary institutions. The purpose of this study was to determine the effect of lecturers without functional positions on the productivity of lecturer research activities. The dependent variable (Y) in this study was the productivity of lecturer research activities, while the independent variable (X) was Lecturers without Functional Positions. The method used is a quantitative descriptive method. The population in this study was 76 permanent lecturers at Universitas Muhadi Setiabudi. Because of the population was less than 100, then all populations were taken as samples. This study used the census method. Data analysis techniques were performed using a One-Way ANOVA method. The results of the study and discussion showed that the average role of lecturers without functional positions has an influence of 83,3% on the productivity of lecturers' research activities.